PENGARUH BIAYA PRODUKSI, BIAYA PROMOSI, VOLUME PENJUALAN, DAN PERILAKU BIAYA TERHADAP PROFITABILITAS PADA PERUSAHAAN FOOD & BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Akirliani, Erika Praja; Afifi, Zaenal; Mulyani, Ulva Rizky (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
Profitability is the ability of a company or business entity to generate profits or profits from its business operations. This study aims to determine the effect of production costs, promotional costs, sales volume, and cost behavior on profitability in food & beverage companies. The population in this study are food & beverage companies listed on the Indonesia Stock Exchange in 2018 - 2022. The resulting sample for 5 years of observation amounted to 117 companies using purposive sampling technique. The results of this study are the variables of production costs and cost behavior have a negative effect on profitability, while the variables of promotional costs, sales volume have a positive effect on profitability